2007
DOI: 10.1063/1.2740184
|View full text |Cite
|
Sign up to set email alerts
|

Generation of cylindrically symmetric converging shock waves by underwater electrical explosion of wire array

Abstract: It is shown that the originally corrugated shock wave generated in the process of an underwater electrical explosion of a cylindrical wire array is self-aligned into a cylindrically symmetric converging front. It was found that by increasing the number of the wires in the array this self-alignment process occurs faster. It is also demonstrated that in the case of a large wire number (>20), one-dimensional calculations can be successfully employed for theoretical analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 6 publications
1
10
0
Order By: Relevance
“…In the vicinity of the exploding wires, one obtains an initially corrugated SW front resulting from the overlapping of individual SWs generated by each wire. In agreement with previously reported results, 35 the originally corrugated SW is self-aligned into a cylindrically symmetric converging front over a very short propagation distance. The fast self-alignment occurs because at this relatively long distance from the axis, the corrugation effect of very short wave-length perturbations greatly exceeds the convergence effect.…”
Section: Results Of Modelingsupporting
confidence: 93%
“…In the vicinity of the exploding wires, one obtains an initially corrugated SW front resulting from the overlapping of individual SWs generated by each wire. In agreement with previously reported results, 35 the originally corrugated SW is self-aligned into a cylindrically symmetric converging front over a very short propagation distance. The fast self-alignment occurs because at this relatively long distance from the axis, the corrugation effect of very short wave-length perturbations greatly exceeds the convergence effect.…”
Section: Results Of Modelingsupporting
confidence: 93%
“…11͒ EOS database for water. When matching the TOF data and the simulated SW trajectory, the simulation results can be used to determine the water parameters at r Յ 3 mm where the SWs generated by the exploding Cu wires overlap each other forming one cylindrical SW. 8 The most interesting of the simulation results are those for r Յ 5 m; namely, the simulations showed two peaks in the values of T and P ͑see Fig. 3͒ and the SW velocity reached ϳ1.5ϫ 10 6 cm/ s. The first peak of ϳ2 ns duration is characterized by T max Ϸ 4200 K, P max Ϸ 130 GPa, max Ϸ 25 MJ/ kg, and max Ϸ 3.4 g / cm 3 .…”
mentioning
confidence: 87%
“…In Ref. 8, it was reported that a wire-array electrical explosion results in the generation of individual SWs that overlap each other forming an azimuthally symmetrical converging SW. Also, it was shown that the energy delivered to the generated water flow is ϳ15% of the stored generator energy. 9 The SW velocity determined using time of flight ͑TOF͒ shadow images of the SW with the known energy deposited into the water flow and the EOS for water were used in hydrodynamic ͑HD͒ simulations of the water parameters behind the SW front.…”
mentioning
confidence: 99%
“…The results of recent research Grinenko et al, 2007;Fedotov et al, 2007;Fedotov-Gefen et al, 2010 on underwater electrical wire array explosions showed that this method can be considered as an alternative to that using light gas guns (Mitchell & Nellis, 1981), Z-pinch (Spielman et al, 1998), powerful lasers (Celliers et al, 2004;Kolacek et al, 2010), or intense heavy ion beams (Tahir et al, 2010) to form warm dense matter (Sasaki et al, 2006). In addition, this method can be especially useful for studying water in extreme states, which is important for studying the physics of giant planets (Lindl et al, 1995;Nellis et al, 1997;Goldman et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, experimental data coupled with hydrodynamic simulations (HD) showed that the efficiency of the energy transfer from the exploding wires to the generated water flow is 20 ± 4% Efimov et al, 2009). Experimental results (Fedotov et al, 2007) showed that the electrical explosion of a cylindrical wire array is accompanied by the generation of a converging strong shock wave (SSW) that is formed as a result of the overlapping of SSWs formed by radially expanding exploding wires. Experimental results (Fedotov et al, 2007) showed that the electrical explosion of a cylindrical wire array is accompanied by the generation of a converging strong shock wave (SSW) that is formed as a result of the overlapping of SSWs formed by radially expanding exploding wires.…”
Section: Introductionmentioning
confidence: 99%